Thromboembolism in Abdominal Aorta due to Spirocerca lupi in a Dobermann Dog - Manickam , Pavithra; Ramalingam, Mahaprabhu; Natesan, Pazhanivel; Rao, Ganne Venkata Sudhakar; Kirubaharan, Jeyaraja; Palavesam, Azhahianambi; Subramaniyan, Subapriya (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
An eight year old female Doberman dog, presented with left limb fracture and paraplegia to the Madras Veterinary College and Teaching Hospital, Chennai revealed a mass in abdominal aorta on ultrasound examination. On worsening of the dog’s clinical condition during the course of clinical intervention, the dog was euthanized on the request of the pet parent. In post mortem examination, nodules measuring around 2 cm diameter were observed in the caudal esophagus. Aortic thromboembolism extending to size of 3-4 cm with live S.lupi worms were observed along with multiple aneurysms. Nodular lesions were also observed on different organs in form of nodules in mediastinal lobe of lung, spleen and urinary bladder due to erratic migration of S.lupi parasites. Histopathologically, aorta revealed multiple necrotizing granuloma extending from tunica intima to tunica media and blood vessels dilatation with thickening of aorta. Muscular layer of esophagus also revealed multiple granuloma containing the L3 stage larvae of S.lupi.